2015
DOI: 10.1080/03602559.2014.1003230
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Curcumin and Curcumin Derivative in Polymeric Nanospheres

Abstract: Curcumin and curcumin derivative were loaded on biocompatible MMA-HEMA copolymeric nanospheres via in-situ microemulsion polymerization. The effect of monomer composition and the emulsifier concentration on the entrapment efficiency (EE), the particle size and zeta potential of the drug loaded-polymeric nanospheres have been studied. The hydrophilic curcumin derivative was loaded with high value reached to about (92±0.5%) against (85±0.8%) recorded for the hydrophobic curcumin. In vitro release of curcumin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Due to the problems of water insolubility and low bioavailability of curcumin or curcumin nanoparticles, it has been reported that biodistribution and bioavailability of curcumin or curcumin nanoparticles would be increased by encapsulation processes such as nanoemulsions, liposomes, micelles, polymeric micro or nanoparticles, phospholipid complexes and hydrogels which showed the potential for efficient drug delivery systems that minimize the delay and reduce the vulnerability of diseases in organisms [44,54,55]. Prasad et al [37] postulated that an increased amount and length of curcumin in blood circulation could enhance the tissue deposition and biological activity in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the problems of water insolubility and low bioavailability of curcumin or curcumin nanoparticles, it has been reported that biodistribution and bioavailability of curcumin or curcumin nanoparticles would be increased by encapsulation processes such as nanoemulsions, liposomes, micelles, polymeric micro or nanoparticles, phospholipid complexes and hydrogels which showed the potential for efficient drug delivery systems that minimize the delay and reduce the vulnerability of diseases in organisms [44,54,55]. Prasad et al [37] postulated that an increased amount and length of curcumin in blood circulation could enhance the tissue deposition and biological activity in animals.…”
Section: Introductionmentioning
confidence: 99%
“…For centuries, it has been popularly used as a food additive and as an herbal medicine in several parts of South Asia [ 28 ]. The United States Food and Drug Administration (USFDA) generally regards curcumin as being safe (GRAS) due to its relatively low toxicity [ 29 ]. Despite its numerous health benefits, its pharmacological or nutraceutical applications are limited due to its poor oral bioavailability and low water solubility [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microemulsion system is the most efficient drug delivery system, which demonstrates high efficiency of drug trapping, release under a sunken environment, biodegradability, and easy removal from the body [2,3]. The microemulsion technique can produce polymer latexes with particle sizes lower than 50 nm, low viscosity, and wide temperature range stability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The microemulsion technique can produce polymer latexes with particle sizes lower than 50 nm, low viscosity, and wide temperature range stability [4,5]. In situ microemulsion polymerization is considered to be an effective method in drug entrapment during the formation of polymer nanosphere [6][7][8]. In the drug delivery application, CNTs were used due to their hollow nanostructures and fantastic physicochemical features [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%